Implementation of triple the time spent on physical education in pre-school to 6th grade: A qualitative study from the programme managers' perspective. (October 2018) - Nielsen, Jonas Vestergaard; Klakk, Heidi; Bugge, Anna; Andreasen, Marianne Løgtholt; Skovgaard, Thomas
Highlights: Involvement of schools in programme content development may improve implementation. School programme promoters help managers address problems at an early stage. A professional development course supports teacher capabilities and motivation. Outdoor physical education supplements limited indoor facilities and resources. Abstract: Schools constitute an important arena for promoting physical activity. However, school-based programmes often face implementation challenges, and the identification of factors influencing the implementation process is considered important in order to secure the effectiveness of future interventions. The aim of this study was to identify factors influencing the various implementation stages during the initial years of a programme tripling the amount of physical education at the primary school level. Document analysis of publicly available programme descriptions and meeting minutes, were conducted. Document analysis was complemented by two semi-structured group interviews with main programme managers to gather in-depth programme experiences and perspectives. Results show that early involvement of schools may ensure the best possible match between programmes and the needs and resources of schools, and that an ongoing shared partnership may help programme managers address program challenges in early stages. It seems that predetermined core elements in programmes are essential. At the same time programmes must be flexible enough for adaptation to individual school contexts. Finally, the implementation of triple the amount of physical education, is supported by teachers receiving a professional development course focusing on how to organise outdoor physical education in different seasons and weather conditions.